Use of ionized monocalcium phosphate and enameline derivatives to reduce dentin hypersensitivity after periondontal therapy = Uso de Fostato Monocálcio y derivados en Enamelina para reducir la hipersensibilidad dentaria después de terapia periodontal - Martínez Aguilar, Víctor Manuel; Peniche Palma, Diana Cecilia; Carrillo Ávila, Bertha Arelly; Sauri Esquivel, Eduardo Almigar; Aguilar Pérez, Fernando Javier (2022)
This study aimed to evaluate the effectiveness of using an ionized monocalcium phosphate and enamelin derivatives (IMP+ED) based mouthwash for the treatment of dentin hypersensitivity (DH) after scaling and root planing (SRP). 47 patients who reported DH after SRP treatment were included in this prospective cohort study. The Schiff Cold Air Sensitivity Scale (SCASS) was applied to classify their degree of pain in mild, moderate or intense at two times: after SRP (T0), and after one month of using a IMP+ED-based mouthwash (T1). The McNemar-Bowker test was used to compare the correlated proportions between both times (p<0.05). After the SRP therapy (T0), all the sample members reported pain distributed in the following manner: 12.8% were mild, 27.6% moderate, and 59.6% intense. At one month since treatment and with the use of the IMP+ED-based mouthwash (T1), the distribution of pain levels changed to 83% mild, 12.8% moderate, and 4.3% intense, this change was statistically significant (p<0.001). IMP+ED-based mouthwash produces a positive effect in reducing painful responses caused by exposure of the dentin tubules to the oral environment after SRP therapy.
El objetivo de este estudio fue evaluar la efectividad de un enjuague bucal a base de fosfato monocálcico ionizado y derivados de enamelina (FCI+DE) para el tratamiento de hipersensibilidad dentinaria (HD) posterior al tratamiento de raspado y alisado radicular (RAR). 47 pacientes que reportaron tener HD posterior al tratamiento de RAR fueron incluidos en este estudio prospectivo de cohorte. Con el fin de clasificar la HD de los pacientes en leve, moderada o intensa se utilizó la Escala de Sensiblidad al Aire Frío de Schiff (ESAFS). Los pacientes fueron evaluados después del tratamiento de RAR (T0) y posterior al uso de un enjuague bucal basado en FCI+DE (T1). Para comparar las proporciones correlacionadas se utilizó la prueba de McNemar-Bowker (p<0.05). La distribución del dolor de los pacientes posterior al tratamiento de RAR (T0) fue la siguiente: 12.8% fueron leves, 27.6% moderado, and 59.6% intenso. Un mes después del uso del enjuague buccal basado en FCI+DE (T1) la distribución en los niveles de dolor cambio a 83% leve, 12.8% moderado, and 4.3% intenso, este cambio fue estadísticamente significativo (p<0.001). El uso del enjuague bucal basado en FCI+DE produce una reducción significativa a la respuesta de dolor causada por la exposición de la dentina al ambiente oral como consecuencia del tratamiento de RAR.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB